Effect of A20 on glucose dependent cell migration in acute lymphoblastic leukemia - Xuan, Nguyen Thi; Chung, Dang Thanh; Mao, Can Van (Vietnam Journal of Biotechnology, 2021)
Acute lymphoblastic leukemia (ALL) is the most common pediatric hematologic malignancy characterized by aberrant proliferation of immature lymphoid cells. A20 is a deubiquitinase gene that inhibits functional activation of immune cells mediated through nuclear factor κB (NFκB)/signal transducers and activators of transcription (STAT) pathways. A20 is frequently inactivated in leukemia/lymphoma. Little is known about the involvement between A20 and STAT signalling in regulating the function of ALL blasts. The present study, therefore, explored whether migration and apoptosis of peripheral blood mononuclear cells (PBMCs) and ALL blasts in high glucose conditions is regulated by A20. To this end, ALL blasts from blood samples of fifteen patients and PBMCs from healthy individuals in the absence of A20 were examined. Gene expression profile was determined by quantitative RT-PCR, cell apoptosis by flow cytometry, and cell migration by a transwell migration assay. As a result, the expression of A20 was inactivated in ALL blasts. Cell migration, but not apoptosis of ALL-blasts was enhanced when the cells were exposed to high glucose and dependent on A20 expression, the effects were abolished by using Nifuroxazide, a STAT inhibitor. In conclusion, A20 inhibited glucose-induced migration of ALL blasts through the STAT pathway. The effect might contribute to poorer survival of ALL patients, who develop hyperglycemia during therapy.